Physiological and biochemical aspects of the avian uropygial gland - Salibian, Alfredo (2009)
This review discusses different aspects of the uropygial gland of birds. The gland exhibits a striking morphological diversity in size, shape and presence/absence of tufts of feathers. It was shown that acidic mucins, neutral lipids, glycolipids and phospholipids are normal components of secretion. Several morphological and physiological aspects of the gland were studied on Rock Pigeon Columba livia Gmelin, 1879. The amount of the uropygial gland secretion, its lipid content and fatty acids profile were determined. The extracted lipid mixture contained of C14 to C20 fatty acids, mostly unsaturated; the saturated fatty acids were mainly 14:0, 16:0 and 18:0. No correlation was found between the size of the gland and the aquatic/terrestrial nature of the species. Ablation of the gland did not affect survival, body weight, feeding rate and serum cholesterol, total lipids or calcium levels after 32-120 days. The possible role of the gland in the protection against lipophilic compounds was discussed. The function of the gland is still a subject of controversy. It is accepted that its secretion confers water-repellent properties on the feather coat and maintain the suppleness of the feathers. Other physiological roles of the gland secretion may be associated to pheromone production, control of plumage hygiene, thermal insulation and defence against predators. Concerning the endocrine regulation of the uropygial function, there is scarce information presenting evidence for steroid regulated mechanisms.